ALLAH TIDAK MENCOBAI “YAKOBUS 1:13” - Asih Purwani; Dicky Kansil (CV. Denasya Smart Publisher, 2024)
The Christian faith believes that trials do not come from GOD. Of course everyone has experienced trials. The trials and tribulations that humans face can make them doubt the existence of God in their lives. James reminds us that humans cannot throw all responsibility for the suffering they experience on God; Although there is indeed suffering that is a test of faith from God, not all human suffering is a test of faith. Some of the suffering experienced by humans is due to their own fault; because humans follow the wrong path and as a result humans have to bear the consequences of their mistakes. James asserts that God cannot be tempted by evil men; in other words, only evil/sinful people test God. Who is such a person? We can see a real example of people like this in the book of Genesis, how Adam and Eve disobeyed God's command. So James says this comes from humans themselves, from sinful desires that are rooted in humans as sinners. It is this sinful desire that drags humans and deceives/deceives humans. Often people misunderstand the difference between trials and tests. From the results, people will usually understand that trials bring death but trials bring growth in faith.